Pengaruh Kenyamanan, Harga, dan Kualitas Produk Terhadap Kepuasan Konsumen Berbelanja di Pasar Klewer Surakarta - Dina Putri Rahayu; Retno Susanti; Setyaningsih Setyaningsih (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Klewer market is the largest textile market in the city of Solo. Klewer market is located next to the Surakarta palace. The aim of this research is to analyze the significance of the influence of comfort, price and product quality on consumer satisfaction shopping at the Surakarta Klewer market. This research uses qualitative data and quantitative data. The data source uses primary data. The population in this research is consumers who shop at the Surakarta klewer market, the exact number of which is not known. The number of samples used in this research is 120 people. The sampling technique uses purposive sampling technique. Data collection techniques use questionnaires, literature study and observation. Data analysis uses descriptive analysis, multiple linear regression test, t test, F test and coefficient of determination test. The results of the multiple linear regression analysis in this study were Y = 3,229 + 0,191 X1 + 0,165 X2 + 0,186 X3. The results of the t test show that the variables of comfort, price and product quality have a significant effect on consumer satisfaction shopping at the Klewer market in Surakarta. The results of the F test in this study have a calculated F value of 29.124 with a significance value (p, value) of 0.000 < 0.05, so Ho rejected and Ha accepted, which means the model used is correct to predict the influence of the independent variables (price convenience and product quality) on the dependent variable (consumer satisfaction). The coefficient of determination test result (R²) for this model is 0.415 or 4.15%, which means the influence of comfort, price and product quality on consumer satisfaction while the remaining 58.5% is influenced by other variables outside this research. The results of the research show that Comfort has a significant influence on consumer satisfaction shopping at the Surakarta Klewer market. Price has a significant influence on consumer satisfaction shopping at the Surakarta Klewer market. Product quality has a significant influence on consumer satisfaction shopping at the Surakarta Klewer market.